AFFECTION OF CSR TO JOB SATISFACTION MEDIATED BY QUALITY OF WORK LIFE (CASE STUDY OF FOUR STAR HOTEL IN INDONESIA) - Adrian, Maria P; Anggiani, Sarfilianty (PEOPLE: International Journal of Social Sciences, 2020)
The purpose of this study is to discuss the perceptions of employees in the hospitality industry on corporate social responsibility and their influence on employee job satisfaction which is mediated by the quality of life of employees. This study hypothesizes about employee job satisfaction with corporate social responsibility mediated by the quality of work life. The population in this study consisted of the hotel industry with 4-star classes working for companies where CSR practices. Methods of data collection include the distribution of survey questionnaires. Using samples taken from four-star hotel employees in DKI Jakarta Indonesia, 175 samples were used as samples for analysis using the Structural Equation Model. The results showed that there are influences of each dimension of CSR (legal, economy, ethical, philanthropic) to the quality of work life. This study also shows the influence of employee job satisfaction to the quality of work-life of employees. There is a mediation of the quality of work-life between CSR dimensions to job satisfaction. This research is expected that the company can find out the needs that must be met by the company for job satisfaction of its employees through CSR activities.